Health benefits, extraction and development of functional foods with curcuminoids. (April 2021) - Munekata, Paulo E.S.; Pateiro, Mirian; Zhang, Wangang; Dominguez, Ruben; Xing, Lujuan; Fierro, Elena Movilla; Lorenzo, Jose M.
Graphical abstract: Highlights: Curcuminoid-rich extracts can be produced with green technologies. Cardiovascular risk can be reduced with regular curcumin consumption. Curcumin can assist in the management of non-communicable diseases. Curcuminoids-rich extracts are promising components for functional food production. Abstract: Turmeric ( Curcuma longa ) is an important condiment used in the culinary of several countries to spice and give a more intense yellow color to food. The importance of this root has gained more attention due to the presence of bioactive compounds known as curcuminoids (the main class of phenolic compounds found in turmeric). The health benefits attributed to curcuminoids are mainly linked to curcumin, the major compound among curcuminoids. Scientific evidence from pre-clinical and clinical trials indicate that turmeric extracts (rich in curcumin) and curcumin can effectively improve the status of subjects by reducing the risk of cardiovascular diseases and diabetes as well as assisting in the management of illness. The present review aims to highlight the use of green extraction technologies to obtain curcuminoid-rich extracts and the health benefits associated with the consumption of turmeric extracts and curcumin (as dietary supplements) against cardiovascular diseases, diabetes, metabolic syndrome, arthritis, and mental disorders at clinical trial level. The current knowledge about the development of functional foods with curcumin is also discussed.